T Cell Adaptive Immunity Proceeds through Environment-Induced Adaptation from the Exposure of Cryptic Genetic Variation - Whitacre, James M.; Lin, Joseph; Harding, Angus (Frontiers in Genetics, 2012)
Evolution is often characterized as a process involving incremental genetic changes that are slowly discovered and fixed in a population through genetic drift and selection. However, a growing body of evidence is finding that changes in the environment frequently induce adaptations that are much too rapid to be accounted for by an incremental genetic search process. Rapid evolution in response to environmental change is hypothesized to be driven by mutations present within the population that are silent or ‘cryptic’ within the first environment but are co-opted or ‘exapted’ to the new environment, providing a selective advantage once revealed. Although the hypothesis that cryptic mutations facilitate evolution was recently confirmed experimentally in RNA enzymes, the role of cryptic mutations in facilitating evolution in complex phenotypes has not been proven. In this paper, we describe the unambiguous relationships between cryptic genetic variation and complex phenotypic responses within the immune system. By reviewing the biology of the adaptive immune system through the lens of evolution, we show that T-cell adaptive immunity constitutes an exemplary model system where cryptic alleles drive rapid adaptation of complex traits. In naive T cells, normally cryptic differences in TCR reveal diversity in activation responses when the cellular population is presented with a novel environment during infection. We summarise how the adaptive immune response presents a well studied and appropriate experimental system that can be used to confirm and expand upon theoretical evolutionary models describing how seemingly small and innocuous mutations can drive rapid cellular evolution.